Real-time PCR identification and detection of Fuscoporia torulosa in Quercus ilex - Campanile, G.; Schena, L.; Luisi, N. (Plant Pathology, 2008)
Fuscoporia torulosa is the causal agent of white alveolar wood decay on several species including a large number of forest trees. Early detection of the fungus is essential to identify diseased trees before spread occurs to healthy plants. However, current detection methods based on isolation from infected tissues on semi-selective media are laborious, time consuming and require expertise in identifying the pathogen after isolation. In the present study, a rapid and reliable Scorpion-PCR based molecular method to identify and detect F. torulosa in planta was developed in a highly polymorphic portion of the internal transcribed spacer (ITS) regions. Specificity of primers and probe was assessed by means of both BLAST analyses and by using genomic DNA from 131 F. torulosa isolates and 43 other fungi and oomycetes from different hosts and geographic areas. In Scorpion-PCR the limit of detection was 1 pg of total DNA and a high correlation (r2 = 0·996) was achieved between target DNA quantity and cycle threshold (Ct). Real-time PCR combined with effective procedures for DNA extraction enabled the detection of F. torulosa from naturally infected tissues of oaks with and without fruit bodies in approximately 6 h. Comparative testing showed that detection of F. torulosa in wood samples is more sensitive and reliable with real-time PCR than with conventional isolation.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: molecular detection; Phellinus torulosus; Scorpion-PCR; white rot; wood decay